EVALUASI DAMPAK PENANAMAN MODAL ASING TERHADAP INDUSTRI PERTAHANAN INDONESIA - Sarjito, Aris (Jurnal EBI, 2023)
The defense sector plays a vital role in safeguarding the sovereignty and security of any nation. In recent years, the Indonesian government has opened up the defense industry to foreign investment to enhance industry competitiveness and technology transfer.The aim of this study is to identify the types and sources of foreign investment in Indonesia's defense industry, assess the extent to which foreign companies are involved in the transfer of technology and know-how to Indonesian firms, evaluate the impact of foreign investment on the competitiveness of Indonesia's defense industry, and identify any potential risks associated with foreign investment in the defense industry. This qualitative study employs a secondary data collection method to identify the types and sources of foreign investment in Indonesia's defense industry, assess the extent of technology transfer to Indonesian firms, evaluate the impact of foreign investment on industry competitiveness, and identify potential risks associated with foreign investment in the defense sector.The research findings indicate that foreign investment has increased the competitiveness of Indonesia's defense industry and enhanced technology transfer. The presence of foreign companies has also led to modernization and up-gradation of the defense sector. However, the study also highlights the potential risks associated with foreign investment, such as intellectual property theft and sensitive technology transfer.Keywords: defense industry, foreign investment, industry competitiveness, potential risks, technology transfer